2020
DOI: 10.1101/2020.07.27.20162578
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pharmacological and Non-Pharmacological Interventions to Enhance Sleep in Mild Cognitive Impairment and Mild Alzheimer’s Disease: A Systematic Review

Abstract: Suboptimal sleep causes cognitive decline and probably accelerates Alzheimer s Disease (AD) progression. Several sleep interventions have been tested in established AD dementia cases. However early intervention is needed in the course of AD at Mild Cognitive Impairment (MCI) or mild dementia stages to help prevent decline and maintain good quality of life. This systematic review aims to summarize evidence on sleep interventions in MCI and mild AD dementia. Seven databases were systematically searched for … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Donepezil hydrochloride plus olanzapine herein significantly improved the cognitive function of patients and considerably relieved the disease condition of patients with Alzheimer's disease [25]. ere was no statistically significant difference in the incidence of adverse reactions between the two groups of patients, which indicated a manageable safety of the combined therapy of donepezil hydrochloride plus olanzapine [26,27].…”
Section: Discussionmentioning
confidence: 88%
“…Donepezil hydrochloride plus olanzapine herein significantly improved the cognitive function of patients and considerably relieved the disease condition of patients with Alzheimer's disease [25]. ere was no statistically significant difference in the incidence of adverse reactions between the two groups of patients, which indicated a manageable safety of the combined therapy of donepezil hydrochloride plus olanzapine [26,27].…”
Section: Discussionmentioning
confidence: 88%
“…Neurodegeneration is accompanied by sleep difficulties due to reduction of amplitude and phase changes of circadian rhythms such as that of melatonin secretion, as well as the disturbing influences of neurodegenerative processes on sleep. The relation between sleep and neurodegenerative diseases is bidirectional and several studies have shown that sleep disruption is a major contributor to neuropathology (30,(73)(74)(75)(76). Alzheimer disease (AD) patients with disturbed sleep-wake rhythms did not only exhibit reduced amounts of melatonin secretions, but also a higher degree of irregularities in the melatonin pattern, such as variations in phasing of the peak.…”
Section: Use Of Exogenous Melatonin In Neurocognitive Disorders: Review Of Evidencementioning
confidence: 99%
“…An emerging symptom of this circadian disruption is "sundowning, " a chronobiological phenomenon observed in patients with AD along with sleep and wakefulness disorder. "Sundowning" is characterized by symptoms appearing in the late afternoon or early evening, which include reduced ability to maintain attention to external stimuli, disorganized speech, and thinking, a variety of motor disturbances including agitation, wandering, and repetitious physical behaviors with emotional disturbances (30,(73)(74)(75)(76).…”
Section: Use Of Exogenous Melatonin In Neurocognitive Disorders: Review Of Evidencementioning
confidence: 99%
“…The findings of these several studies demonstrated that, despite some statistical limitations, there is sufficient evidence to suggest that CPAP treatment may be effective in improving cognition in OSA patients with MCI and AD. Moreover, treating sleep apnea holds great promise not only to enhance cognition but also to improve quality of life and delay MCI and AD progression [ 73, 74 ]. For instance, several studies demonstrated that OSA increases AD biomarker burden and as such, it is plausible to hypothesize that CPAP treatment would also result in changes of amyloid and tau AD biomarkers.…”
Section: The Effects Of Cpap Therapy On Cognitionmentioning
confidence: 99%